ANALISA KUALITAS ESTETIS BRANDED GOODS DENGAN TEORI DESIGN SYNTACTIC FORM - Devanny Gumulya (Jurnal Da Moda, 2020)
Product with good aesthetic appearance increases the consumer attractiveness and create memorable product experience. The paper discusses how the design element and the configuration can shape someone’s visual perception with syntactic design form theory, gestalt theory, and product gist method. Using these three approaches, two international bag brand is selected as study cases: Anya Hindmarch and Kate Spade. The study results are material, and the color design element can be continuously changed according to the trend, but the shape proportion and the configuration between the design elements need to be consistent. So the brand will still look coherent visually. By using this strategy, these two brands stay competitive and favorable in the market.